Ubiquitination of RIPK1 regulates its activation mediated by TNFR1 and TLRs signaling in distinct manners - Xingyan Li; Mengmeng Zhang; Xinyue Huang; Wei Liang; Ganquan Li; Xiaojuan Lu; Yanxia Li; Heling Pan; Linyu Shi; Hong Zhu; Lihui Qian; Bing Shan; et al. (Nature Communications, 2020)
RIPK1 is a critical kinase which mediates necroptosis, apoptosis and inflammation. Regulation of RIPK1 by ubiquitination is being intensively investigated. Here, the authors made knock-in RIPK1-K612R mice and demonstrate that this mutation alters the RIPK1 ubiquitinylation pattern and inhibits its prodeath kinase activity in response to TNFα but sensitizes cell death to TLRs signals.